A Summary of Studies of the Pazyryk Culture by Chinese Scholars - Mu Jinshan (Поволжская археология)
This article is divided into two parts and examines Pazyryk culture from the perspective of Chinese scholars. The first part includes the translation and publication of foreign language works, which can be divided into two phases: government-led (period 1950–1980) and spontaneous translation by Chinese scholars in the 21st century. The second part directly describes the research of Chinese scholars on the Pazyryk culture. Chinese scholars have done a lot of work, but some problems remain. The most important one is that Chinese researchers do not fully understand the Pazyryk culture. The reason for this is that Chinese researchers are not sufficiently know about scientific works of Soviet and Russian scientists. In order to understand the direction of future research, we should analyse the process of Pazyryk culture research in China.